Professional Development on Digital Literacy for Teachers in Early Childhood Education in the Digital Era - Farisia, Hernik; Syafi'i, Imam (Tafkir: Interdisciplinary Journal of Islamic Education, 2024)
The demand for teachers’ digital literacy competencies has become a worldwide concern in transforming education in the digital era, as technology has become an important part of the teaching and learning process. Therefore, this study aimed to identify how sustainable teacher development impacts teachers’ digital literacy competencies. This study used a qualitative approach with interviews, questionnaires, documentation, and Focus Group Discussions (FGD) as instruments to gather data. The findings showed that preschool teachers’ digital literacy improved, particularly in their ability to create digital content for learning. The strategy to enhance preschool teachers’ digital literacy was conducted through a sustainable professional development scheme that placed the teacher community at its center, serving as a medium for teachers to develop their professional abilities. The program focused on three main schemes to improve teachers’ digital literacy skills: (1) self-development through Wakelet training to assist teachers in managing digital content in collaboration with other teachers, (2) conducting research-based learning to improve the quality of learning, and (3) fostering teacher innovation in developing teaching media that integrates technology into learning practices. The results of this study provide a significant contribution to exploring the schemes for preschool teachers’ professional development in improving digital literacy skills. Future research could capture more creative solutions to technical challenges in sustaining teachers’ professional development programs.